An Analysis of Student's Reading Motivation in Reading Subject at English Department of Universitas Negeri Padang - Atikah Indah Arridha; Don Narius (Universitas Negeri Padang, 2019)
AbstractReading is an important activity that cannot be separated from human’s activity. As a student, reading becomes a vital aspect for helping them toward the learning. However, there are many factors that steal students’ attention from reading. In this research, the researcher wanted to find out how students’ motivation in this recent situation. The purpose of this study was aimed to analyse the students’ reading motivation and defined the type of students’ motivation in reading subject at English Department of UNP. The study was descriptive study using quantitative approach. The data were collected through a ready-made questionnaire “Motivation Reading Questionnaire” by Wigfield and Guthrie (1997). The subject of the study was 2016 English Education students from English Department of UNP. The samples of the study were chosen by using cluster random sampling technique. The result of this study showed that: (1) 2016 English Education Students have a good motivation in reading, because a half of the participant were in average level of reading motivation, followed by the high level of motivation, and there were only two students who have low motivation, (2) the students’ type of motivation were dominantly extrinsic motivation.